EXTREME RAIN EVENTS ASSOCIATED WITH THE RISKS OF FLOODS IN ARACAJU, SERGIPE - Duarte, Thiago Lima Santana; Santos, Gabriel Carvalho; Castelhano, Francisco Jablinski (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1089, 2021)
Chaotic urban growth has led to the existence of risk scenarios caused, among others, by climatic factors. In Aracaju, capital of the state of Sergipe, northeastern Brazil, this reality does not seem to differ from the other medium and large Brazilian municipalities affected by extreme precipitation events. Thus, this article aimed to analyze the occurrence of rain events and their relationship with floods and inundations at the urban area of ​​Aracaju. With the treatment of historical data series collected from the official meteorological station of the National Institute of Meteorology (INMET), data from the Municipal Civil Defense and from journalistic records of the local press, it was possible to analyze, from a systemic perspective, how the dynamics of urban space production ​​has reflected in socio-environmental issues for disregarding the seasonality of precipitation events.